1992
DOI: 10.1105/tpc.4.7.759
|View full text |Cite
|
Sign up to set email alerts
|

Premature dissolution of the microsporocyte callose wall causes male sterility in transgenic tobacco.

Abstract: Male sterility in a petunia cytoplasmic male sterile line has been attributed to the early appearance of active callase, a P-1,3-glucanase, in the anther locule. This leads to premature dissolution of the callose walls surrounding the microsporogenous cells. We have mimicked this aspect of the petunia line in transgenic tobacco by engineering the secretion of a modified pathogenesis-related vacuolar P-1,3-glucanase from the tapetum prior to the appearance of callase activity in the locule. Plants expressing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
137
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 286 publications
(140 citation statements)
references
References 33 publications
2
137
0
1
Order By: Relevance
“…In many other plants and in normal pollen development, soon after meiosis, cell separation generally occurs to release the free microspores from the tetrads (Figure 4.1E and F). During this process, a decrease of pH (Izhar and Frankel, 1971;Worrall et al, 1992) and a peak of β-(1,3)-glucanase activity were observed in the anther locular fluid (Stieglitz, 1977) suggesting that this enzyme may be involved in the degradation of the tetrad wall. Degradation of the callose wall requires a complex of endo-and exo-enzymes, called callase.…”
Section: Microspore Separationmentioning
confidence: 99%
See 4 more Smart Citations
“…In many other plants and in normal pollen development, soon after meiosis, cell separation generally occurs to release the free microspores from the tetrads (Figure 4.1E and F). During this process, a decrease of pH (Izhar and Frankel, 1971;Worrall et al, 1992) and a peak of β-(1,3)-glucanase activity were observed in the anther locular fluid (Stieglitz, 1977) suggesting that this enzyme may be involved in the degradation of the tetrad wall. Degradation of the callose wall requires a complex of endo-and exo-enzymes, called callase.…”
Section: Microspore Separationmentioning
confidence: 99%
“…A tight developmental regulation is de facto required to synchronize the production of wall-degrading enzymes by the tapetal cells with the maturation of the PMCs. Indeed, the premature dissolution of the callose wall or premature programmed cell death of the tapetum, which normally occurs during the late pollen formation, lead generally to a reduction in male fertility (Worrall et al, 1992;Tsuchiya et al, 1995;Ku et al, 2003). Several possible callase members have been described.…”
Section: Microspore Separationmentioning
confidence: 99%
See 3 more Smart Citations